Contribution of ferroptosis and GPX4’s dual functions to osteoarthritis progression - Miao, Yu; Chen, Yiwei; Xue, Feng; Liu, Kexin; Zhu, Bin; Gao, Junjie; Yin, Junhui; Zhang, Changqing; Li, Guangyi (EBioMedicine, 2022)
Osteoarthritis (OA) is the most common joint disease and is the leading cause of chronic disability among older people. Chondrocyte death and extracellular matrix (ECM) degradation was involved in OA pathogenesis. Ferroptosis was an iron-dependent cell death associated with peroxidation of lipids. Here, we proved that ferroptosis exists in OA and identified glutathione peroxidase 4 (GPX4) as an important regulator of OA. Ferroptosis-related alterations were analyzed in human OA and undamaged cartilage. Expression of GPX4 was examined in 55 paired human OA samples. Ferrostatin-1 (Fer-1) and Deferoxamine (DFO) were used to treat OA, in vitro and in vivo. Alterations of GPX4-mediated signaling pathway were identified by RNA-seq analysis. AAV-Gpx4-shRNA were used to downregulate GPX4 expression in vivo. Transcriptomic, biochemical, and microscopical analyses indicated that ferroptosis was closely associated with OA. Expression of GPX4 in the OA cartilage from 55 OA patients were significantly lower than undamaged cartilage. Fer-1 and DFO could protect OA in a necroptosis-independent manner, suggesting that ferroptosis exists in OA prog. Importantly, GPX4 downregulation could increase the sensitivity of chondrocytes to oxidative stress and aggravate ECM degradation through the MAPK/NFκB pathway. Furthermore, downregulation of GPX4 expression by AAV-Gpx4 shRNA aggravated OA in vivo. Ferroptosis contributes to OA pathogenesis and GPX4 was the intersection of two mechanisms in regulating OA progression: ferroptosis and ECM degradation. This work was supported by the Projects of International Cooperation and Exchanges of National Natural Science Funding of China (Grant no. 81820108020), the National Key Research and Development Project of China (Grant no. 2018YFC1106300) and the Basic Science Program of Shanghai Jiao Tong University Affiliated Sixth People's Hospital (Grant no. ynms202102).